Peculiarities of Introducing Geoinformation System in the Monitoring Procedure of Rangelands in the Republic of Armenia - Hovhannisyan, T. A.; Efendyan, P. S. (ՀԱԱՀ հիմնադրամ)
Animal husbandry is one of the leading agricultural branches in Armenia. Throughout recent years, almost 40 % of the agricultural gross product is resulted from the animal husbandry branch. The rangelands play a crucial role in the forage base development. In the recent 30 years the pastures in Armenia have lost their qualitative properties due to overgrazing and degradation thereof, while the land types with the characteristic traits of grasslands are not often used for their intended purpose. It is practically impossible to implement monitoring over the rangelands without clear and constantly updated information. Such kind of information can be retrieved via the use of geoinformation systems.
Keywords: Agricultural Engineering